Trademarks as an Indicator of Product and Marketing Innovations - Millot, Valentine (OECD Publishing, 2009)
Non-technological innovation is a major factor of competitiveness and productivity growth in the economy, notably in the service industries. However, the measurement of non-technological innovation and of innovation in the service industries is currently very poor, as traditional data sources like R&D or patents do not apply to these types of innovations. This document presents a strong candidate for quantifying non-technological innovation: trademark data. Trademarks constitute a rich and easily accessible source of data. Besides, several studies have shown that they are highly correlated with various innovation variables (patents, share of innovative sales). Lastly, trademarks have a large perimeter of application; they are present in almost every sector of the economy. Trademark data are then likely to convey information on two key (overlapping) aspects of innovation that are not well covered by traditional indicators: innovation in the service sectors and marketing innovation. This paper aims at presenting trademarks, their potential link with innovations and their main statistical properties, to see if they may actually serve as an innovation indicator
Keywords: Science and Technology